1983
DOI: 10.2134/jeq1983.00472425001200020027x
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Phosphorus in Sludge‐Affected Soils

Abstract: Phosphorus accumulated in sludge‐treated soils was chemically fractionated by a sequential extraction procedure. Samples used for the study were obtained from experimental plots of a sludge land application site, where composted sludges at rates 0, 22.5, 45, and 90 t ha−1 y−1, and liquid sludges at rates of 0, 3.75, 7.5, and 15 cm/y have been applied for 5 y. There were also experimental plots whose liquid sludge treatments were terminated after 3 y. The experimental field was cropped with winter barley (Horde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 0 publications
4
33
0
2
Order By: Relevance
“…This confirms the report of Chang et al (1983) that five continuous years of biosolids application in two California soils at 0, 22.5, 45 and 90 ton per hectare increased the total P concentration of surface soil (0-15 cm) from 515-540 mg/kg to 1092-1312, 1657-2163 and 2617-3470 mg/kg, respectively. Similarly Maguire et al (2000) reported that the concentration of total soil P in surface soils (0-20 cm) of biosolid amended soils was 738 mg/kg, or nearly double the values in unamended soils, where the total soil P was 403 mg/kg.…”
Section: Mapping and Estimation Of Chemical Concentrations In Surfacesupporting
confidence: 91%
“…This confirms the report of Chang et al (1983) that five continuous years of biosolids application in two California soils at 0, 22.5, 45 and 90 ton per hectare increased the total P concentration of surface soil (0-15 cm) from 515-540 mg/kg to 1092-1312, 1657-2163 and 2617-3470 mg/kg, respectively. Similarly Maguire et al (2000) reported that the concentration of total soil P in surface soils (0-20 cm) of biosolid amended soils was 738 mg/kg, or nearly double the values in unamended soils, where the total soil P was 403 mg/kg.…”
Section: Mapping and Estimation Of Chemical Concentrations In Surfacesupporting
confidence: 91%
“…High TP concentration in the sludge sourced from detergents may affect decomposition because they have a negative impact on microbial activities with some of these detergents being biocides; hence inhibiting microbial activities in the FS which may be beneficial to the degradation processes (Block et al, 2001;Kawasaki et al, 2002). Phosphorous immobilizes other chemicals like zinc and copper that are essential for microbial life, making the reported concentrations a cause of concern to the beneficial microorganisms for faecal sludge degradation (Chang et al, 1983). The documented TP concentrations justify the need for further treatment of the FS as the current concentration would lead to algal growth, odour and oxygen depletion if the sludge is disposed into water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…2. Actually, after sludge spreading, mineral forms of phosphorus are likely to link to iron or aluminium present in soil (Chang et al, 1983), while organic forms are rapidly hydrolysed, both in acid or basic soils (Hinedi et al, 1989). Most sludges induce a decrease in the binding capacity of soil to phosphate ions, as soon as they are incorporated into soil, but it is not the case for limed sludges, which lead to an increase of this binding capacity.…”
Section: Discussionmentioning
confidence: 99%